Triassic faunal successions of the Paraná Basin, southern Brazil. (December 2020) - Schultz, Cesar L.; Martinelli, Agustín G.; Soares, Marina B.; Pinheiro, Felipe L.; Kerber, Leonardo; Horn, Bruno L.D.; Pretto, Flávio A.; Müller, Rodrigo T.; Melo, Tomaz P.
Abstract: The Paraná Basin was filled by a sedimentary package deposited in successive sedimentation episodes related to the tectonic events that hit the SW portion of the Gondwana. The Triassic portion of this package, known worldwide for its continental tetrapod fauna, occurs only in the southern portion of the basin and is represented by 2 s-order sequences: the Sanga do Cabral Supersequence (SCS - Early Triassic) and the Santa Maria Supersequence (SMS - Middle-Late Triassic). The SCS fauna, including temnospondyls, parareptiles (mainly Procolophon ), archosauromorphs, putative synapsids, and a number of indeterminate specimens, is traditionally considered Early Triassic and corresponds to the " Procolophon abundant zone" of the Karoo Basin (the upper levels of the Lystrosaurus AZ), in the upper Katberg Formation, which is Induan to early Olenekian in age. The sedimentary environment of the SCS is thought to be a wide alluvial plain, in which small and shallow channels spread northwards into a vast semiarid environment. By its turn, the Middle-Upper Triassic Santa Maria Supersequence is divided into four third-order sequences, from base to top: Pinheiros-Chiniquá, Santa Cruz, Candelária and Mata. Each of these sequences begins with fluvial deposition (low sinuosity rivers) that is overlain by transgressive shallow lacustrine deposits. The first three of these sequences present a very rich record of fossil tetrapods, including four successive faunal associations: Dinodontosaurus Assemblage Zone (Ladinian, within the Pinheiros-Chiniquá Sequence), Santacruzodon AZ (Ladinian/Carnian, in the Santa Cruz Sequence), Hyperodapedon AZ (Carnian) and the Riograndia AZ (early Norian), the latter two respectively at the base and top of the Candelária Sequence. In general, the lower portion of the package (Pinheiros-Chiniquá and Santa Cruz Sequences) was deposited under more basic and dried environmental conditions and are dominated by synapsids, while the top of the section (Candelária Sequence) is characterized by more acid and humid conditions and by a shift in the faunal content, with diapsids as dominating forms and presenting an increase of diversity compared to the lower biozones. Highlights: In Brazil, Triassic tetrapods are known only in the extreme south of the country. The south Brazilian Triassic package includes four biozones based on tetrapods. The lower tetrapod biozone of the Triassic package is Early Triassic and corresponds to the " Procolophon abundant zone" of the Karoo Basin. Lower portion of the Middle-Late Triassic was deposited under more basic and dried environmental conditions and is dominated by synapsids. Upper portion of the Middle-Late Triassic is characterized by more acid and humid conditions and presents an increase of diapsids compared to the lower portion.